2018
DOI: 10.1017/s1751731118001933
|View full text |Cite
|
Sign up to set email alerts
|

Review: Nutrigenomics of marbling and fatty acid profile in ruminant meat

Abstract: The present review will present the recent published results and discuss the main effects of nutrients, mainly fatty acids, on the expression of genes involved in lipid metabolism. In this sense, the review focuses in two phases: prenatal life and finishing phase, showing how nutrients can modulate gene expression affecting marbling and fatty acid profile in meat from ruminants. Adiposity in ruminants starts to be affected by nutrients during prenatal life when maternal nutrition affects the differentiation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 105 publications
2
51
1
2
Order By: Relevance
“…The pathway analysis revealed that genes involved in fatty acid metabolism, the peroxisome proliferator-activated receptors (PPAR) signaling pathway, and steroid biosynthesis were enriched ( Figure 2 B). Interestingly, we found that the expressions of key enzymes in fatty acid metabolism such as fatty acid synthase ( fasn) and salicylate decarboxylase ( scd) [ 31 ], were downregulated in the OF-fed group. We also found lysyl oxidase like 2 (loxl2), a gene that involved in liver fibrosis [ 32 ] as well as the sterol O-acyltransferase 1 ( soat1 ), a potential biomarker for hepatocellular carcinoma [ 33 ], were also downregulated by OF.…”
Section: Resultsmentioning
confidence: 99%
“…The pathway analysis revealed that genes involved in fatty acid metabolism, the peroxisome proliferator-activated receptors (PPAR) signaling pathway, and steroid biosynthesis were enriched ( Figure 2 B). Interestingly, we found that the expressions of key enzymes in fatty acid metabolism such as fatty acid synthase ( fasn) and salicylate decarboxylase ( scd) [ 31 ], were downregulated in the OF-fed group. We also found lysyl oxidase like 2 (loxl2), a gene that involved in liver fibrosis [ 32 ] as well as the sterol O-acyltransferase 1 ( soat1 ), a potential biomarker for hepatocellular carcinoma [ 33 ], were also downregulated by OF.…”
Section: Resultsmentioning
confidence: 99%
“…In ruminants, glucose is one of the main forces triggering lipogenesis and marbling, and it also plays a key role in providing fuel for cellular and tissue functions. In this regard, mechanisms involved in the glucose absorption in the small intestine, liver gluconeogenesis, and glucose retention by the tissues are essential to produce high marbling meat and to increase meat quality traits in ruminants (Ladeira et al, ). Lee, Park, Kim, Yoon, and Seo (), studying metabolic differences between muscle and intramuscular adipose tissues in the Longissimus dorsi of Hanwoo beef cattle, identified the propanoate metabolism downregulated in the intramuscular adipose tissue.…”
Section: Resultsmentioning
confidence: 99%
“…En concordancia con los resultados obtenidos, Pfaffl et al (21), obtuvieron mayor contenido de grasa intramuscular y expresión del gen igf1 en novillos Simmental alimentados con silo de maíz con respecto a novillos alimentados con pastura y heno. Asimismo, Ladeira et al (22) demostraron que la expresión del gen glut4 en el músculo esquelético puede ser alterada incorporando suplementos en las dietas. En este sentido, Hocquette et al (5) sugieren que las dietas basadas en granos aumentan la conversión de glucosa en grasa intramuscular, en comparación con dietas basadas en pasto, explicando los resultados obtenidos.…”
Section: Discussionunclassified